THE ROLE OF INTEGRATION OF PHYSICS AND ENGLISH IN INCREASING EDUCATIONAL EFFICIENCY IN PHYSICS LESSONS - N.Z.Mamadaliyeva (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation.This article explores the pedagogical potential and practical benefits of integrating the English language into physics instruction. It argues that a bilateral approach—teaching  physics  through  English-not  only  enhances  students'  language proficiency but also deepens their understanding of physical concepts. By examining the  methodologies  for  creating  a  bilingual  learning  environment,  the  article demonstrates how this integration fosters critical thinking, improves access to global scientific  resources,  and  better  prepares  students  for  international  academic  and professional collaboration. The study concludes that the synergy between language and science education significantly increases the overall efficiency of the physics lesson, making  learning  more  contextual,  engaging,  and  relevant  to  modern  globalized standards.